PEMBELAJARAN KIMIA MELALUI METODE EKSPERIMEN BERBASIS LINGKUNGAN ALAM SEKITAR DITINJAU DALAM PERSPEKTIF ISLAM - Buchori Muslim; Zulfiani Zulfiani; Dedi Irwandi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
This paper aims at describing teaching and learning activities in chemistry lesson through environmental-based (contextual-based) experiments that are viewed from the perspective of Islam. Islam teaches its followers to study their environment in order to find solution for many problems. One of the problems posed by chemistry teachers with regards to conducting chemistry experiments is the lack of laboratory equipments. In fact, if environment has been studied well, Islam has provided anything we need including the need to conduct chemistry experiment. Verses in Quran, especially al-Baqarah: 185, an-Nisa: 28, al-Hajj: 78, and Hud: 61 implied that our environment provides more than enough for us to do experiments. The problem of not doing the experiments was that because teachers are not studying their environment well enough. This paper describes some ideas in which environment helps chemistry teachers to be able to conduct chemistry experiments without losing the chemistry concept. DOI: 10.15408/tjems.v1i2.1267